Revision of Brada Stimpson, 1853, and Bradabyssa Hartman, 1967 (Annelida, Flabelligeridae) - Salazar-Vallejo, Sergio I. (Zootaxa, 2017)
Among flabelligerid genera Brada Stimpson, 1853 includes several species whose bodies are fusiform or club-shaped, often with a reduced number of chaetigers, and their members are found in temperate and polar waters. In contrast, Bradabyssa Hartman, 1967 is regarded as a monotypic genus with a single Antarctic species with a cylindrical body and a variable number of chaetigers. After examination of all type and non-type material available of both genera, two distinct body patterns were distinguished: one includes the type species for Brada, B. granosa Stimpson, 1853, has only 8 branchial filaments and the neurochaetae are thick, blunt, often falcate, whereas the other includes the type species of Bradabyssa, B. papillata Hartman, 1967, usually has many branchial filaments and neurochaetae are straighter and mucronate. Consequently, Brada is herein restricted to include only 5 species, one of which is new, Brada kudenovi n. sp. Bradabyssa is herein emended to include many species formerly regarded as belonging in Brada, as new combinations, and species can be separated into four groups according to the development of the tunic and its sediment load. Thirteen new species of Bradabyssa are also described: B. indica n. sp., B. mexicana n. sp., B. alaskensis n. sp., B. elinae n. sp., B. grangieri n. sp., B. levensteinae n. sp., B. harrisae n. sp., B. hartmanae n. sp., B. jirkovi n. sp., B. kirkegaardi n. sp., B. monnioti n. sp., B. mezianei n. sp. and B. willeyi n. sp. The species belonging to Brada are B. granosa, B. granulosa Hansen, 1880, B. incrustata Støp-Bowitz, 1948, B. inhabilis (Rathke, 1843), and B. kudenovi n. sp. The species belonging to Bradabyssa are separated into four groups according to the development of their tunic and its sediment load. Group crustosa includes B. indica n. sp., B. mexicana n. sp., B. minuta (Amoureux, 1986) n. comb., and B. sachalina (Annenkova-Chlopina, 1922) n. comb. Group nuda includes B. alaskensis n. sp., B. antarctica (Hartman, 1978) n. comb., B. bransfieldia (Hartman, 1966) n. comb., B. nuda (Annenkova-Chlopina, 1922) n. comb., B. rugosa (Hansen, 1880) n. comb., and B. strelzovi (Jirkov & Filippova in Jirkov, 2001) n. comb. Group verrucosa contains B. abyssalis (Fauchald, 1972) n. comb., B. annenkovae (Buzhinskaja, 2001) n. comb., B. elinae n. sp., B. grangieri n. sp., B. irenaia (Chamberlin, 1919) n. comb., B. levensteinae n. sp., B. mammillata (Grube, 1877) n. comb., B. ochotensis (Annenkova-Chlopina, 1922) n. comb., B. papillata Hartman, 1967, B. tenebricosa (Berkeley, 1966) n. comb., n. status, and B. verrucosa (Chamberlin, 1919) n. comb. Group villosa contains B. capensis (Day, 1961) n. comb., n. status, B. harrisae n. sp., B. hartmanae n. sp., B. ilyvestis (Hartman, 1960) n. comb., B. intoshi (Caullery, 1944) n. comb., B. jirkovi n. sp., B. kirkegaardi n. sp., B. monnioti n. sp., B. parthenopeia (Lo Bianco, 1893) n. comb., B. pilosa (Moore, 1906) n. comb., B. pluribranchiata (Moore, 1923) n. comb., B. setosa (Verrill, 1873) n. comb., B. mezianei n. sp., B. tzetlini (Jirkov & Filippova in Jirkov, 2001) n. comb, B. villosa (Rathke, 1843) n. comb., B. whiteavesi (McIntosh, 1885) n. comb and B. willeyi n. sp. Keys to aid identification of all genera in Flabelligeridae, to species in Brada, and for the species belonging in the four species groups of Bradabyssa are included.